Analisis Strategi Pengelolaan Hutan Rakyat Berbasis Skema Forest Stewardship Council untuk Mitigasi Dampak Deforestasi (Studi Kasus di Forest Management Unit Wana Semeru Agung, Lumajang) - Wenddy Adiguna; Hendrata Wibisana; Hervina Puspitosari (Universitas Trunodjoyo Madura, 2026)
The deforestation rate in the buffer zone of Bromo Tengger Semeru National Park (TNBTS) poses a serious threat to the stability of the local ecosystem. This study aims to analyze land cover dynamics and evaluate community forest management strategies based on the Forest Stewardship Council (FSC) scheme as a deforestation mitigation instrument at FMU Wana Semeru Agung, Lumajang. The research contribution is providing a comprehensive analysis of the integration between international certification standards and local policies in maintaining the buffer zone of a conservation area. The method employed is mixed methods, combining spatial analysis and William N. Dunn’s policy evaluation model. The results indicate that the integration of FSC standards has significantly suppressed deforestation rates, with open land area successfully reduced to 0 Ha during the 2023-2024 period. This strategy proved ecologically effective through the implementation of agroforestry systems and economically efficient, with 98% of farmers reporting an increase in income. In conclusion, the FSC scheme is effective as a site-level deforestation mitigation instrument, although the